(untitled) (CAHIERS MAGELLANES-NS, 2024)
Blended learning, which integrates traditional face-to-face instruction with online learning, has gained popularity as an educational model. The study examined the relationship between pupil characteristics and learning outcomes and investigated the effectiveness of blended learning. The article endeavors to identify important factors that influence academic sccess in this learning environment by analyzing data from a diverse cohort of students enrolled in integrated learning courses. Education systems worldwide are progressively transitioning to e-learning paradigms as the digital age continues to advance. Additionally, the development of policies and practices that facilitate the effective implementation of blended learning can be informed by this knowledge, thereby improving educational equity and effectiveness. It is imperative to address these issues in order to optimize the potential of integrated learning and guarantee that all students have the chance to flourish in this innovative educational model. Furthermore, the investigation underscores the significance of instructional design and support mechanisms in optimizing the advantages of integrated learning. The implications of these discoveries for educators and policymakers are examined, offering a perspective on how blended learning can be optimised to meet the diverse requirements of students and improve the overall effectiveness of education.